Tecendo sequências didáticas de geometria para trabalhar a maranhensidade nos anos iniciais do ensino fundamental - VALE, Mônica Letícia Sousa (2024)
The Guidelines and Bases of National Education Act (LDBEN/GBNEA), Law no. 9.394/96, determines that curricula must be composed of a common national base and a diversified part. In 2018, the National Common Curricular Base (BNCC/NCCB) was established. In 2019, the state of Maranhão published the Curricular Document of the Territory of Maranhão (CDTMA), in line with the LDBEN/GBNEA. This document seeks to address the needs of the students of Maranhão, based on their regional context and unique features. The study is about what is stated in the DCTMA upon the development of “maranhesity” together with the school mathematics. This research is part of the umbrella project The production of didactic sequences for the teaching of mathematics in early childhood education and elementary school: “maranhensity” as a core axis, coordinated by Professor Dr. Jónata Ferreira Moura, within the scope of the research group Histories of Teacher Training of Math Teachers (Hifopem). The research is of qualitative approach, research-action type, having as locus a class of the 5th grade of Elementary School in a municipal public school of Imperatriz/MA, and merging the “maranhensity” with the teaching of the thematic unit of geometry as part of the mathematics curricular component. The research question is: Having the “maranhensity” as the focus, and identifying the students attached significations to it, how do the produced/proposed didactic sequences favor the learning of the thematic unit of geometry as part of the mathematics curricular component of the students of the early years of Elementary School. The objectives are: 1. To analyze, in light of the historical-cultural theory, the proposals of both the National Common Curricular Base (NCCB/BNCC) of 2018 and the Curricular Document of the Territory of Maranhão (CDTMA/DCTMA) of 2019 for the teaching of mathematics for the initial years of Elementary School; 2. To understand how the teaching of the thematic unit of geometry as part of the mathematics curricular component is proposed by the BNCC and the DCTMA; 3. Having the “marenhensity” as the core axis, to develop didactic sequences upon the teaching of the thematic unit of geometry as part of the mathematics curricular component, in line with the BNCC and the DCTMA guidelines, for students in the 5th year of Elementary School; 4. To analyze how the generated didactic sequences favor the learning of the thematic unit of geometry as part of the mathematics curricular component for students in the early years of Elementary School and what are their attached significations to it. Data production was carried out through video recordings of teaching sequences which were transcribed in the researcher's field diary, and was guided by micro genetic analysis.